The educational game "MARIO" for early childhood number recognition to improve cognitive abilities: Attempts and Problems - Budiarti, Erna; Lestari, Juwita Tri; Hagenimana, Emmanuel (Journal of Teaching and Learning Mathematics, 2024)
This research aims to explore the use of the educational game "MARIO" in improving the cognitive capacity of young children, especially in number recognition. "MARIO" is an acronym for Marble, Number, Recreational, Innovative, and Observation, each element of which is integrated with the game to create a fun learning experience. This research involved 30 students aged 4-6 years in a kindergarten in Jakarta. Data collection is carried out through observation, interviews, and documentation, known as the OWI method. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion. The results showed that the "MARIO" game significantly improved children's cognitive abilities in recognizing numbers. The three stages of number recognition include recognizing numbers through marbles (Marbel), matching numbers with number cards (Numbers), and movement activities involving numbers (Recreative). In the observation stage, children record the results of their play, which helps in understanding the concepts of comparison and measurement. Of the 30 students, 85% showed improvement in basic numeracy skills, with an average improvement of 30% in the basic math skills test. This research concludes that the integration of educational elements in the "MARIO" game is not only effective in improving children's cognitive abilities but also makes the learning process more interesting and enjoyable. Thus, "MARIO" can be recommended as an innovative learning aid for early childhood.